2021
DOI: 10.1177/12034754211049711
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Use in Pediatric Patients With Hidradenitis Suppurativa: A Systematic Review

Abstract: Background: There is currently at least 1 biologic (adalimumab) approved in North America for treatment of Hidradenitis Suppurativa in the pediatric population. However, no reviews or clinical trials have specifically analyzed the effectiveness and safety data of biologic use in this population. The objective of this systematic review is to identify and summarize the outcomes of biologic therapy in pediatric patients with HS. Methods: MEDLINE and EMBASE databases were used to conduct the search on Sept 18, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
7
0
5
Order By: Relevance
“…The US Food and Drug Administration has approved the use of adalimumab in patients 12 years or older, with a dosing regimen of 40 mg every other week or 40 mg every week for obese or refractory adolescents. 18 A recent review of MEDLINE and EMBASE databases identified 12 pediatric HS patients treated with biologic treatment with good response. Seven patients experienced complete resolution of their HS, whereas 5 patients had partial resolution.…”
Section: Immunosuppressorsmentioning
confidence: 99%
See 4 more Smart Citations
“…The US Food and Drug Administration has approved the use of adalimumab in patients 12 years or older, with a dosing regimen of 40 mg every other week or 40 mg every week for obese or refractory adolescents. 18 A recent review of MEDLINE and EMBASE databases identified 12 pediatric HS patients treated with biologic treatment with good response. Seven patients experienced complete resolution of their HS, whereas 5 patients had partial resolution.…”
Section: Immunosuppressorsmentioning
confidence: 99%
“…18 A case report described a 16-year-old adolescent girl who showed strong clinical and psychological improvement with adalimumab use for 4 years, with no adverse effects. 18 Literature on infliximab or etanercept use in pediatric HS is scarce, but in a case series, 1 pediatric patient demonstrated subjective improvement with etanercept. 18 Although oral steroids and methotrexate are used in the adult literature, these medications are not typically used in pediatric HS unless the presentation is severe.…”
Section: Immunosuppressorsmentioning
confidence: 99%
See 3 more Smart Citations